Gut Microbiota On Erectile Dysfunction : a Systematic Review - Dwiprawira, Revantoro Artha; Bintoro, Ariyo Sakso (Green Publisher Indonesia, 2025)
Erectile dysfunction (ED) has significant physical and psychological effects on both patients and their partners. Beyond disrupting sexual relationships and family dynamics, ED is often associated with comorbidities such as anxiety, depression, and other mental health disorders. A potential relationship is suggested by variations in our gut microbiota the composition between ED patients and healthy people. This study aims to evaluated relationship between gut microbiota and ED. Materials & Methods : A systematic review was conducted with PRISMA 2020 guidelines, with PICO framework to focus on individuals with ED. The intervention analyzed was gut microbiota compared to healthy controls, with the primary outcome being gut microbiota associated with ED. Search was performed across PubMed, Scopus, Web of Science, and Cochrane Library from 2020 to 2025 using keywords such as